KEDUDUKAN ANAK ANGKAT DALAM PEWARISAN MENURUT HUKUM ADAT BATAK KARO DI DESA AJIBUHARA KECAMATAN TIGA PANAH KABUPATEN TANAH KARO - Yopita Arihta; Ulfia Hasanah; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Humans created god in the two types of men and women who have an interest and need each other to form a marital bond to form a family. Inheritance system is one way of transfer of ownership of property and material rights of the heir to the heir. Inheritance law karo society is patrilineal patrilineal, the division of his estate is also distinguished. Legacy that is not moving, such as land, houses given to boys, while the legacy that moves like pakean and gold given to the woman. Giving legacy is the biological child of the testator. While the child who is a foster child inheritance obtained limited to the proceeds of livelihood and excluding inheritance. The existence of a foster child in the middle of the Batak Karo interesting to discuss because if the adoptive parents died boys are entitled to inherit from his adoptive parents.This study is the direct legal research sociological researchers to conduct research on the location completely and clearly about the issues examined by interviewing the head and the Karo Batak Karo Batak people. The result of this study is the first that the village Ajibuhara a foster son has fully inherited the position and rights of property search adoptive parents but are not entitled to inherit treasures like biological children through the procedures and customary provisions applicable. Second, the implementation of village Ajibuhara adoption should be done with the intent to bring the event adatdengan other communities know that there has been no event of adoption of the village. Suggestions of this study is the first, to the people who have adopted children in order to perform all procedures according to customary adoption and inheritance so that the position adopted child becomes clear. Second, the traditional dean Karo Batak society to be more prudent in deciding the adoption community.Keywords: Position Adopted, Heritage, Batak Karo, Customary Law